2019
DOI: 10.1038/s41598-019-47091-x
|View full text |Cite
|
Sign up to set email alerts
|

Stumbling reactions in hypo and hyper gravity – muscle synergies are robust across different perturbations of human stance during parabolic flights

Abstract: The control of bipedal stance and the capacity to regain postural equilibrium after its deterioration in variable gravities are crucial prerequisites for manned space missions. With an emphasize on natural orthograde posture, computational techniques synthesize muscle activation patterns of high complexity to a simple synergy organization. We used nonnegative matrix factorization to identify muscle synergies during postural recovery responses in human and to examine the functional significance of such synergie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…mechanical) or internal (e.g. aging or pathology) perturbations to locomotion, the number of synergies is not affected in both mice (Santuz et al, 2019) and humans (Maclellan et al, 2014; Santuz et al, 2018b, 2020a; Holubarsch et al, 2019; Janshen et al, 2020). Several studies have attempted in the past to highlight potential discrepancies between overground and treadmill locomotion from many perspectives concluding that spatiotemporal, kinematic, kinetic, and muscle-tendon interaction measures are scarcely influenced by the locomotion environment (Van Hooren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…mechanical) or internal (e.g. aging or pathology) perturbations to locomotion, the number of synergies is not affected in both mice (Santuz et al, 2019) and humans (Maclellan et al, 2014; Santuz et al, 2018b, 2020a; Holubarsch et al, 2019; Janshen et al, 2020). Several studies have attempted in the past to highlight potential discrepancies between overground and treadmill locomotion from many perspectives concluding that spatiotemporal, kinematic, kinetic, and muscle-tendon interaction measures are scarcely influenced by the locomotion environment (Van Hooren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2014; Santuz et al, 2018aSantuz et al, , 2020aHolubarsch et al, 2019;Janshen et al, 2020). Several studies have attempted in the past to highlight potential discrepancies between overground and treadmill locomotion from many perspectives concluding that spatiotemporal, kinematic, kinetic, and muscle-tendon interaction measures are scarcely influenced by the locomotion environment (Van Hooren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the human stance during PF maneuvers compared to 1 g- conditions revealed the similarity of postural recovery responses in 1 g -, hypo- and hyper-gravity conditions 17 . These results showed that muscle synergies and segmental strategies acquired on Earth are robust and persistent across variable acute changes in gravitation 17 .…”
mentioning
confidence: 90%
“…The Guest Edited Collection ‘ Gravitational biology and space medicine ’ includes publications reporting on health concerns for astronauts and cosmonauts 1416 during space missions, and physiological changes caused by short-term µ g 17 . Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 .…”
mentioning
confidence: 99%